[Analyses de] - S. Magnavita, L. Koté, P. Breunig & A. I. Idé, Crossroads/Carrefour Sahel. Cultural and technological developments in first millennium BC/AD West Africa. Africa Magna Verlag, Frankfort, Journal of African Archaeology Series, Vol. 2 - (:unkn) unknown (My University, 2010)
Book review of S. Magnavita, L. Koté, P. Breunig & A. I. Idé, Crossroads/Carrefour Sahel. Cultural and technological developments in first millennium BC/AD West Africa, 2009
Keywords: African Research